2022
DOI: 10.1186/s12879-022-07080-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of intra-partum azithromycin on carriage of group A streptococcus in the Gambia: a posthoc analysis of a double-blind randomized placebo-controlled trial

Abstract: Background Group A Streptococcus (GAS) is a major human pathogen and an important cause of maternal and neonatal sepsis. Asymptomatic bacterial colonization is considered a necessary step towards sepsis. Intra-partum azithromycin may reduce GAS carriage. Methods A posthoc analysis of a double-blind, placebo-controlled randomized-trial was performed to determine the impact of 2 g oral dose of intra-partum azithromycin on maternal and neonatal GAS ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The collection of 501 global SDSE sequences included publicly available short-read sequence data from NCBI sequence read archive (SRA) and complete genome assemblies from NCBI RefSeq until 4 May 2022. These included studies of invasive and non-invasive SDSE from Japan 43 , 48 , 49 , Germany 50 , India 51 , China 52 , Canada 23 , Norway 24 , 34 , 44 , USA 18 , 19 , Denmark 53 , Switzerland 54 and The Gambia 55 . A further 228 invasive and non-invasive isolates were collected from Australia, France, USA, India, Argentina, Trinidad, Japan, Fiji, and Portugal to maximise geographical diversity.…”
Section: Methodsmentioning
confidence: 99%
“…The collection of 501 global SDSE sequences included publicly available short-read sequence data from NCBI sequence read archive (SRA) and complete genome assemblies from NCBI RefSeq until 4 May 2022. These included studies of invasive and non-invasive SDSE from Japan 43 , 48 , 49 , Germany 50 , India 51 , China 52 , Canada 23 , Norway 24 , 34 , 44 , USA 18 , 19 , Denmark 53 , Switzerland 54 and The Gambia 55 . A further 228 invasive and non-invasive isolates were collected from Australia, France, USA, India, Argentina, Trinidad, Japan, Fiji, and Portugal to maximise geographical diversity.…”
Section: Methodsmentioning
confidence: 99%
“…The collection of 501 global SDSE sequences included publicly available short-read sequence data from NCBI sequence read archive (SRA) and complete genome assemblies from NCBI RefSeq until 4 May 2022. These included studies of invasive and non-invasive SDSE from Japan [47][48][49] , Germany 50 , India 51 , China 52 , Canada 23 , Norway 24,34,43 , USA 18,19 , Denmark 53 , Switzerland 54 and The Gambia 55 . A further 228 invasive and non-invasive isolates were collected from Australia, France, USA, India, USA, Argentina, Trinidad, Japan, Fiji, and Portugal to maximise geographical diversity.…”
Section: Bacterial Isolatesmentioning
confidence: 99%
“… 13 , 15 , 16 Instead, there are concerns about infection with azithromycin-resistant bacteria. 17 , 18 Animal studies have shown a link between antenatal azithromycin exposure and development concerns of multiple organ systems in fetus. 19 , 20 Observational studies have shown an association between antenatal azithromycin exposure and increased risk of stillbirth and congenital malformations in infants, raising serious safety concerns.…”
Section: Introductionmentioning
confidence: 99%